Synthesis and evaluation of self-calibrating ratiometric viscosity sensors - Yoon, Hyung-Jo (2011)
We describe the design, synthesis and fluorescent profile of a family of self-calibrating dyes that provide ratiometric measurements of fluid viscosity. The design is based on covalently linking a primary fluorophore (reference) that displays a viscosity-independent fluorescence emission with a secondary fluorophore (sensor) that exhibits a viscosity-sensitive fluorescence emission. Characterization of fluorescent properties was made with separate excitation of the units and through Resonance Energy Transfer from the reference to the sensor dye. The chemical structures of both fluorophores and the linker length have been evaluated in order to optimize the overall brightness and sensitivity of the viscosity measurements. We also present an application of such ratiometric dyes for the detection of membrane viscosity changes in a liposome model.